Structure modification properties of glucosamine sulphate in osteoarthritis: problems and prospects - Hochberg, Mark K. (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article contains results, which were made public by Prof. M.K. Hochberg at the annual OARSI World Congress on October 23, 2010, by his kind permission. Results of randomized clinical researches are analysed, and these confirm efficacy of glucosamine sulphate, manufactured by Rottapharm, for treating knee joint osteoarthritis at the level of 73 %. Prospects for studying the effect, produced by structurally modified drugs in patients with osteoarthritis, are shown.